Potentia dei absoluta et potentia dei ordinata u Orygenesa? Nowa próba wyjaśnienia kontrowersyjnych fragmentów "De principiis" - Mrugalski, Damian (Vox Patrum, 2018)
The medieval dispute over the absolute and the ordered, power of God (potentia Dei absoluta et potentia Dei ordinata) began with a tract by Peter Damian entitled De divina omnipotentia. One of the questions posed in this work was whether God could indeed do everything, including those things that God did not in fact do. The same question, and a similar answer, appears in Origen’s work Contra Celsum: God can do everything except that which is evil. The impossibility of doing evil, however, does not diminish the omnipotence of God, because evil, is by its very nature, non-being. Beyond that, Origen, in numerous statements appearing in his exegetical works, distinguishes between the absolute power of God, which is infinite, and the power of God that creates the world and operates within it, which has a certain God-given limit – that is, this power is adapted to the abilities of the creatures who receive it. The purpose of this article is to show that, in the light of the distinction of the potentia Dei absoluta and the potentia Dei ordinata, fragments of De principiis (II 9.1 and IV 4.8), in which a finite world and finite power of God are posited, can be interpreted in a new way. Many contemporary scholars, on the basis of these fragments, conclude that Origen inherited from the Greek philosophers a negative understanding of infinity as something imperfect, but the analysis carried out in this article shows something different. In talking about a certain range of God’s power, which is available to creatures, or in which creatures participate only partially, Origen does not actually exclude the proposition that, in God himself, power – existing in an absolute way – can be infinite.